COBIT 2019 Framework in IT Governance: A Systematic Literature Review of Implementation Challenges and Benefits Across Various Industry Sectors - Muhammad Deagama Surya Antariksa; Maria Perangin Angin; Aris Puji Widodo (Journal of Renewable Energy, Electrical, and Computer Engineering, 2025)
Information technology (IT) governance is a critical factor in ensuring that IT investments align with business objectives, improve operational efficiency, and mitigate risks across various industries. COBIT 2019, a widely used IT governance framework, has been adopted in numerous sectors to address these needs. This study explores the implementation of COBIT 2019 by conducting a systematic literature review (SLR) of 23 relevant articles published between 2020 and 2024, sourced from internationally indexed journals. The research focuses on identifying the challenges, benefits, success factors, and strategies to mitigate the issues encountered during the implementation of COBIT 2019. The findings indicate that COBIT 2019 has been successfully applied in diverse industries such as education, healthcare, logistics, and mineral mining, demonstrating its flexibility and adaptability to different organizational contexts. Key benefits include improved alignment of IT with business strategies, enhanced risk management, better resource optimization, and increased operational efficiency. However, challenges such as the complexity of the framework, limited resources, and a lack of understanding of the frameworks terminology have been identified. Successful implementation is largely dependent on strong management support, stakeholder engagement, and adequate resource allocation. Mitigation strategies such as ongoing training, development of comprehensive communication plans, and regular evaluation of IT governance practices have been suggested to overcome these challenges. This study provides practical insights into the implementation of COBIT 2019, offering organizations guidance on maximizing its benefits while addressing the barriers to successful implementation.